Integrating Islamic Values in Science Education: A Critical Pedagogy Insight through Systematic Literature Network Analysis - Arina Zaida Ilma; Dwi Purbowati (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2026)
Integration of Islamic values in natural science education is essential. It forms learning not only focuses on cognitive or pure science aspects but also develops students’ morals, ethics, and spirituality. In the context of science education, Islamic values can help students understand that science is not only aimed at exploring the physical world but also invites them to think about the ethical and spiritual implications of the resulting technology and innovation. The study aims to analyze the integration of Islamic principles in science education to provide students with a holistic and ethical approach to learning science. The methods used Systematic Literature Network Analysis (SLNA) to identify trends, connections, and gaps in the literature on Islamic values in science education. Fifty-four articles (N = 54) recorded in Scopus databases from 2014 to 2024 were analyzed using Vos Viewer and Biblioshiny software. The findings indicate that Islamic values in science education are integrated through critical pedagogical processes that connect scientific concepts with Islamic ethics and real-life contexts via discussion, inquiry, and communication, as shown by the systematic literature network analysis. Recommendations are offered to educators and policymakers to develop curricula that integrate Islamic values into science education. Further research can expand this field and its practical applications in Islamic-based schools and higher education.